Financial Evaluation of Sugar Cane Production Experince in Diyala Province - Almubarak, Nadir F.; Al-Mayahi, Mhana. A.; Zaidan, Ali G. (Diyala Agricultural Sciences Journal, 2020)
Despite the economic and nutritional importance of the sugar cane crop as a strategic crop، its cultivation and production in Iraq is still below the required level of self-sufficiency due to the growing demand for its uses، Hence the motivation of researchers to cultivate this important strategic crop for the first time in Diyala province located in the eastern part of central Iraq to contribute to improve the local production، therefore the research aimed at assessing the efficiency of the performance of these projects in the province A year of productivity 2018، through the study of indicators and economic efficiency criteria. The results of the study of the economic criteria used for the total projects considered that all the projects studied were of technical feasibility، with economic profit amounted to about 26410.5 thousand dinars، but net cash income amounted to 34145 thousand dinars، and The investor has reached 1.755 dinars and a productivity of 75.5%، which means that the single dinar generates a profit of 755 fils، and a simple rate of return of 75.5%، which reflects the efficiency of the projects to achieve economic profits during the productive year، as for the period of capital recovery was 1.280 years ، That is، the period when the product recovers good and short، the parity point standard as a ratio of 0.23% which low and this reflects the high production safety ، As for the employment rate، it was about 0.569، which is low، and finally the productivity of the changing capital is about 2.23 dinars. We conclude from the study of sugar cane projects that it has achieved economic and technical feasibility and the investment opportunities that are meaningful and have good economic returns and therefore the study recommends the need to invest in these projects because of the revenues and profits and the contribution to the supply of the national product in quantities of production.